Making sense of Heidegger : a paradigm shift - Sheehan, Thomas (London : Rowman & Littlefield International, 2015)
'In this brilliant contribution to Heidegger scholarship, Thomas Sheehan presents his view of the entire trajectory of Heideggers philosophizing as a phenomenological investigation of the meaning and source of Being (the'clearing') that which allows entities to show up for us as meaningful. Sheehans assiduously phenomenological interpretation of the Heideggerian corpus lends itself beautifully both to teaching Heidegger and to interdisciplinary inquiry.' (Robert D. Stolorow Ph. D., author of World, Affectivity, Trauma: Heidegger and Post-Cartesian Psychoanalysis).
Frequently Cited German Texts and their English Translations. Foreword -- Introduction: Getting to the Topic. Part I: Aristotelian Beginnings Being in Aristotle -- Heidegger Beyond Aristotle. Part II: The Early Heidegger. Phenomenology and the Formulation of the Question -- Ex-sistence as Openness -- Becoming Our Openness. Part III: The Later Heidegger. Transition: From Being and Time to the Hidden Clearing --Appropriation and the Turn -- The History of Being. Conclusion: Critical Reflections. Appendices -- Bibliographies --Index.
Includes bibliographical references and index.
Keywords: Heidegger, Martin, -- 1889-1976.